A hierarchical filtration smnf / mxene-ss composite membrane and a preparation method and application thereof

CN122899079APending Publication Date: 2026-10-13ANHUI FUCHUN COLOR TEXTILE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611408836.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0002]现有MXene基复合膜材料虽然具有较高的导电性和电磁屏蔽潜力,但在实际应用中仍存在若干问题:其一,MXene片层之间界面结合较弱,易发生堆叠、剥离或导电通路破坏,导致材料结构稳定性不足;其二,MXene在水和空气环境中容易发生氧化,进而引起导电性能和功能保持性下降;其三,单纯通过均质混合或直接涂覆方式构筑的复合膜往往存在成膜完整性较差、层间作用不足以及功能组分分布无序等问题,难以同时兼顾力学性能、导电性能和环境稳定性

Benefits of technology

1.本发明通过采用分层抽滤策略,实现丝胶-MXene导电组分和蚕丝微纳米原纤组分的有序层状组装,有利于MXene片层在抽滤过程中定向沉积并形成连续导电网络,从而提升导电性能;同时有助于增强层间接触与界面结合,使SMNF的骨架支撑作用、丝胶蛋白的界面调控与稳定化作用以及MXene的导电功能得到更充分发挥。此外,分层抽滤构建的有序多层结构能够在保证成膜完整性的同时,增强导电相之间的有效连接,减少导电组分无序聚集带来的不利影响,在改善界面作用的同时增加层间协同作用,提升材料的结构稳定性和功能保持性,使复合膜体系在导电性、稳定性及应用性能方面表现更优,解决了现有技术中MXene基功能材料结构稳定性不足、界面结合不佳及性能保持性有限的问题,从而实现了材料综合性能的提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899079A_ABST
    Figure CN122899079A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of layered composite materials, and particularly relates to a layered filtration SMNF / MXene-ss composite film and a preparation method and application thereof. By adopting a layered filtration strategy, ordered layered assembly of the silk gum-MXene conductive component and the silk micro-nano fibril component is realized, the effective connection between the conductive phases is enhanced, the adverse effects caused by the disordered aggregation of the conductive component are reduced, the interface action is improved, the interlayer synergistic action is increased, the structural stability and the functional retention of the material are improved, the composite film system performs better in terms of conductivity, stability and application performance, and has application prospects in rewritable conductive paper, paper-based circuits, humidity sensing materials, flexible electromagnetic shielding materials and thermal management materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of layered composite material technology, specifically to a layered filtration SMNF / MXene-ss composite membrane, its preparation method, and its application. Background Technology

[0002] While existing MXene-based composite membrane materials possess high conductivity and electromagnetic shielding potential, several problems remain in practical applications: First, the interfacial bonding between MXene layers is weak, making them prone to stacking, peeling, or disruption of conductive pathways, resulting in insufficient material structural stability. Second, MXene is easily oxidized in water and air environments, leading to a decline in conductivity and functional retention. Third, composite membranes constructed solely through homogeneous mixing or direct coating often suffer from poor film integrity, insufficient interlayer interaction, and disordered distribution of functional components, making it difficult to simultaneously achieve mechanical properties, conductivity, and environmental stability.

[0003] Natural silk micro / nanofibrils (SMNFs) possess excellent flexibility, mechanical support, and abundant interfacial active sites, making them suitable as a reinforcing framework for layered composite membranes. MXene can serve as the primary conductive functional phase, endowing the composite membrane with excellent conductivity and functional responsiveness; sericin can play a role in interfacial regulation and stabilization of MXene. Therefore, constructing an ordered layered composite membrane using SMNFs, sericin, and MXene through a layered filtration process holds promise for improving the problems of insufficient interfacial bonding, poor structural stability, and inadequate long-term functional retention in existing technologies. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a layered filtration SMNF / MXene-ss composite membrane, its preparation method, and its application.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a stratified vacuum filtration SMNF / MXene-ss composite membrane includes the following steps: Step (1): Add sericin to MXene aqueous dispersion and disperse evenly to obtain sericin-MXene conductive dispersion; Degummed silk was added to a eutectic solvent for liquid phase exfoliation, and then water was added to disperse it evenly to obtain a silk micro-nano fibril dispersion. Step (2): Take sericin-MXene conductive dispersion as the filtrate for MXene-SS conductive layer; take silk micro-nano fibril dispersion as the filtrate for SMNF layer. The SMNF dispersion and the sericin-MXene conductive dispersion were alternately vacuum filtered in layers, so that the SMNF layer and the MXene-ss conductive layer were deposited one after another, forming a structure in which the SMNF layer and the MXene-ss conductive layer were arranged alternately. After peeling and drying, the layered filtration SMNF / MXene-ss composite membrane was obtained.

[0006] In the above steps, by adopting a layered filtration strategy, the ordered layered assembly of the sericin-MXene conductive component and the silk micro / nano fibrillary component is achieved. This facilitates the directional deposition of MXene sheets during filtration and the formation of a continuous conductive network, thereby improving conductivity. Simultaneously, it helps enhance interlayer contact and interfacial bonding, allowing the skeletal support of SMNF, the interfacial regulation and stabilization of sericin, and the conductive function of MXene to be more fully utilized. Furthermore, the ordered multilayer structure constructed by layered filtration can enhance the effective connection between conductive phases while ensuring film integrity, reducing the adverse effects of disordered aggregation of conductive components, improving interfacial interactions, increasing interlayer synergy, and enhancing the structural stability and functional retention of the material. This results in a composite membrane system exhibiting superior conductivity, stability, and application performance.

[0007] Preferably, in step (1), when preparing the sericin-MXene conductive dispersion, the mass ratio of MXene to sericin protein is (0.8-1.2):1; the specific process for uniform dispersion includes stirring at 250-350 rpm for 3-5 hours.

[0008] Furthermore, the mass ratio of MXene to sericin is 1:1.

[0009] Furthermore, the rotation speed was 300 rpm, and the stirring time was 4 hours.

[0010] Preferably, in step (1), when preparing the sericin-MXene conductive dispersion, the concentration of the MXene aqueous dispersion is 8-12 mg / mL.

[0011] Furthermore, the concentration of the MXene aqueous dispersion was 10 mg / mL.

[0012] Preferably, in step (1), when preparing the sericin-MXene conductive dispersion, the preparation process of the MXene aqueous dispersion includes the following steps: adding Ti3AlC2MAX phase powder to LiF / HCl etching solution, stirring and reacting, centrifuging after the reaction, washing the precipitate until the pH of the system is 6, redispersing the obtained precipitate in water, ultrasonically peeling, centrifuging and enriching to obtain the MXene aqueous dispersion.

[0013] Furthermore, the preparation process of the LiF / HCl etching solution includes: adding 3.2g of LiF to 40mL of 9mol / L HCl aqueous solution and stirring at room temperature for 30min.

[0014] Furthermore, the stirring reaction conditions are: stirring reaction at 36℃ for 24h; the ultrasonic peeling conditions are: ultrasonic peeling at 0℃ for 1h.

[0015] Preferably, in step (1), when preparing the silk micro-nano fibril dispersion, the mass ratio of degummed silk to eutectic solvent is 1:(90-110).

[0016] Furthermore, the mass ratio of degummed silk to eutectic solvent is 1:100.

[0017] Preferably, in step (1), when preparing the silk micro-nano fibril dispersion, the specific process of liquid phase stripping treatment includes: liquid phase stripping treatment for 2-4 h at a temperature of 70-90 ℃ and a stirring speed of 300-500 rpm.

[0018] Preferably, the specific process for uniform dispersion in step (1) of preparing the silk micro-nano fibril dispersion includes: mechanical dispersion at room temperature and a rotation speed of 6500-7500 rpm for 20-40 min.

[0019] Furthermore, the rotation speed was 7000 rpm and the mechanical dispersion time was 30 min.

[0020] Preferably, in step (1), when preparing the silk micro / nano fiber dispersion, the preparation process of the eutectic solvent includes the following steps: mixing urea, choline chloride and water in a molar ratio of (5.5-6.5):(2.5-3.5):(0.8-1.2) and stirring at a temperature of 110-130℃ and a speed of 350-450rpm for 0.5-1h.

[0021] Furthermore, the molar ratio of urea, choline chloride, and water is 6:3:1.

[0022] Furthermore, the temperature was 120℃, the rotation speed was 400rpm, and the stirring time was 1h.

[0023] Preferably, in step (1), when preparing the silk micro-nano fiber dispersion, the preparation process of degummed silk includes the following steps: placing natural silk in a 5% Na2CO3 aqueous solution, degumming it at 100°C for 1 hour at a bath ratio of 1:50, and then taking it out. Repeat the above degumming process once more. After the degumming process is completed, wash it with deionized water until neutral and dry it to constant weight.

[0024] Preferably, the specific process of alternating vacuum filtration in step (2) includes the following steps: The SMNF dispersion and the sericin-MXene conductive dispersion were arranged in a layer sequence with alternating SMNF and MXene-SS conductive layers, and the outermost layer was always an SMNF layer. The layers were then subjected to alternating vacuum filtration to deposit and composite the layers sequentially.

[0025] Furthermore, in step (2), the stratified SMNF / MXene-ss composite membrane has an alternating arrangement structure of SMNF layer / MXene-ss conductive layer / SMNF layer or an alternating arrangement structure of SMNF layer / MXene-ss conductive layer / SMNF layer / MXene-ss conductive layer / SMNF layer.

[0026] Preferably, a layered filtration SMNF / MXene-ss composite membrane is prepared using the layered filtration SMNF / MXene-ss composite membrane preparation method described above.

[0027] Preferably, the application of a layered filtration SMNF / MXene-ss composite membrane as described above on rewritable conductive paper.

[0028] Preferably, the application of a layered filtration SMNF / MXene-ss composite membrane as described above in paper-based circuits, humidity sensing materials, flexible electromagnetic shielding materials, or thermal management materials.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention employs a layered filtration strategy to achieve the ordered layered assembly of sericin-MXene conductive components and silk micro / nano fibrils. This facilitates the directional deposition of MXene sheets during filtration, forming a continuous conductive network and thus improving conductivity. Simultaneously, it enhances interlayer contact and interfacial bonding, allowing the skeletal support of SMNF, the interfacial regulation and stabilization of sericin, and the conductive function of MXene to be fully utilized. Furthermore, the ordered multilayer structure constructed by layered filtration ensures film integrity while enhancing effective connections between conductive phases, reducing the adverse effects of disordered aggregation of conductive components. It improves interfacial interactions and increases interlayer synergy, enhancing the structural stability and functional retention of the material. This results in a composite membrane system with superior conductivity, stability, and application performance, solving the problems of insufficient structural stability, poor interfacial bonding, and limited performance retention in existing MXene-based functional materials, thereby achieving a comprehensive improvement in material performance.

[0030] 2. This invention improves the overall performance of the composite membrane material through the synergistic effect of SMNF, sericin, and MXene. This synergistic effect is mainly reflected in the following performance aspects: Firstly, electrical conductivity is improved. MXene, as the main conductive functional phase, provides an electron transport pathway; SMNF, as a fibrous framework, helps to support and disperse conductive components; and sericin helps to improve the interfacial contact between MXene and SMNF. The synergy of these three components facilitates the formation of a continuous and stable conductive network, thereby improving the overall electrical conductivity of the material.

[0031] Secondly, structural stability and film integrity are improved. SMNF provides skeletal support, enhancing the overall structure of the membrane; sericin plays a role in interfacial regulation, bridging, and adhesion between components; and MXene sheets participate in the construction of the composite layered structure. The synergy of these three components facilitates the formation of a continuous, tightly interfacial composite membrane, thereby improving the film-forming properties and structural stability of the material.

[0032] Third, mechanical properties are improved. SMNF provides a flexible fiber support network, sericin enhances interlayer adhesion and stress transfer, and MXene sheets provide some constraint and reinforcement against deformation in the composite structure. This allows for more effective stress dispersion and transfer under external forces, thereby improving the material's strength, integrity, and durability.

[0033] Fourth, humidity sensing performance is improved. The fiber network and porous structure of SMNF facilitate the adsorption and diffusion of water molecules, the hydrophilic groups in sericin enhance the material's sensitivity to humidity changes, and the MXene conductive network can convert the interfacial interactions and charge transport changes caused by humidity changes into detectable electrical signals. The synergistic effect of these three factors makes it easier for the material to obtain a stable and significant humidity response.

[0034] Fifth, functional retention and operational stability are improved. Sericin has a stabilizing and protective effect on MXene, helping to slow down the decay of conductivity; SMNF helps maintain overall structural stability; and MXene is responsible for functional realization. The combined effect of these three factors makes it easier for the material to maintain stable performance during storage, copying, and sensing.

[0035] In summary, the improvements in conductivity, film integrity, structural stability, mechanical properties, humidity sensing performance, copy conductivity, and functional retention of the stratified SMNF / MXene-ss composite membrane can all be attributed to the synergistic effect of SMNF as a framework support, sericin as an interface regulator and stabilizer, and MXene as a conductive agent.

[0036] 3. The composite film prepared in this invention, when combined with a paper-based material, can be used to create rewritable conductive paper. Under external pressure, the sericin-MXene conductive component migrates to the surface of the target paper and forms a conductive path, while the SMNF framework helps maintain the stability of the original composite film structure, allowing the material to achieve conductive pattern copying while retaining a certain degree of reusability. Therefore, this synergistic effect enables the material to possess both copy imaging and conductive output capabilities. Specifically, the process of combining the SMNF / MXene-SS composite film with the paper substrate is as follows: after drying the prepared layered filtration composite film, one side of the composite film is used as the non-transfer surface and bonded to the paper substrate, while the other side is used as the transfer surface facing outwards. Subsequently, the composite film-based rewritable conductive paper is obtained by pressing and drying. The composite film and paper substrate are fixed by pressing and drying to form a rewritable conductive paper. Although MXene-ss is located in the middle layer, the layered composite structure formed by layered filtration is interpenetrating. Under pressure, the conductive components of MXene-ss near the transfer surface can migrate locally through the surface SMNF fiber network and be deposited on the target paper surface, thereby achieving conductive transfer. Attached Figure Description

[0037] Figure 1 This is a comparison of the surface morphology of the pure SMNF membrane prepared in Comparative Example 1 and the SMNF / MXene-ss composite membrane prepared in Example 1. In the figure, a is a scanning electron microscope image of the pure SMNF membrane prepared in Comparative Example 1, and b is a scanning electron microscope image of the SMNF / MXene-ss composite membrane prepared in Example 1. Figure 2 This is a comparison of the cross-sectional morphology of the pure SMNF membrane prepared in Comparative Example 1 and the SMNF / MXene-ss composite membrane prepared in Example 2 in this invention; in the figure, a is the cross-sectional morphology of the pure SMNF membrane prepared in Comparative Example 1, and b is the cross-sectional morphology of the SMNF / MXene-ss composite membrane prepared in Example 2. Figure 3 These are SEM images, elemental composition and elemental distribution characterization diagrams of the pure SMNF membrane prepared in Comparative Example 1 of this invention; in the figures, a is the SEM image of the pure SMNF membrane, b is the surface distribution diagram of C element in the pure SMNF membrane, c is the surface distribution diagram of N element in the pure SMNF membrane, d is the surface distribution diagram of O element in the pure SMNF membrane, and e is the elemental distribution characterization diagram of the pure SMNF membrane. Figure 4These are SEM images, elemental composition, and elemental distribution characterization diagrams of the SMNF / MXene-ss composite film prepared in Example 1 of this invention; in the figures, a is the SEM image of the SMNF / MXene-ss composite film, b is the surface distribution diagram of C element in the SMNF / MXene-ss composite film, c is the surface distribution diagram of N element in the SMNF / MXene-ss composite film, d is the surface distribution diagram of O element in the SMNF / MXene-ss composite film, e is the surface distribution diagram of Ti element in the SMNF / MXene-ss composite film, and f is the elemental distribution characterization diagram of the SMNF / MXene-ss composite film. Figure 5 This is a comparison of the infrared spectra of the pure SMNF membrane and the SMNF / MXene-ss composite membrane in this invention; in the figure, a is the infrared spectrum of the pure SMNF membrane, and b is the infrared spectrum of the SMNF / MXene-ss composite membrane. Figure 6 This is a comparison of the XPS full spectrum of the pure SMNF membrane and the SMNF / MXene-ss composite membrane in this invention; in the figure, a is the XPS full spectrum of the pure SMNF membrane, and b is the XPS full spectrum of the SMNF / MXene-ss composite membrane. Figure 7 The figures show the mechanical property test results of the pure SMNF membrane prepared in Comparative Example 1, the SMNF / MXene-ss composite membrane prepared in Examples 1 and 2, and a photograph of the homogeneous mixed SMNF / MXene-ss composite membrane prepared in Comparative Example 2. In the figures, a is the mechanical property test result of Comparative Example 1, b is the mechanical property test result of Example 1, c is the mechanical property test result of Example 2, and d is a photograph of Comparative Example 2. Figure 8 These are the conductivity test results and surface resistance comparison analysis diagrams of the SMNF / MXene-ss composite films prepared in Examples 1 and 2 of this invention; in the figures, a is the conductivity test result diagram of Example 1, b is the conductivity test result diagram of Example 2, and c is the surface resistance comparison analysis diagram of Example 1 and Example 2. Figure 9 This is a comparison diagram of the electromagnetic shielding performance of the pure SMNF film prepared in Comparative Example 1 and the SMNF / MXene-ss composite film prepared in Example 1 in this invention; in the figure, a is the electromagnetic shielding performance test result diagram of Comparative Example 1, and b is the electromagnetic shielding performance test result diagram of Example 1. Figure 10 This is a graph showing the humidity sensing performance test results of the SMNF / MXene-ss composite membrane prepared in Example 2 of this invention; in the graph, a is the fitting curve of the composite membrane resistance versus RH in the range of 33%~97%RH, and b is the resistance graph of the composite membrane under the same relative humidity after 4 cycles. Figure 11 This is a graph showing the respiratory monitoring performance test results of the SMNF / MXene-ss composite membrane prepared in Example 2 of this invention; Figure 12 The figure shows the thermal management performance test results of the SMNF / MXene-ss composite membrane prepared in Example 2 of this invention; in the figure, a is the skin temperature without the SMNF / MXene-ss composite membrane, and b is the skin temperature with the SMNF / MXene-ss composite membrane. Detailed Implementation

[0038] The present invention will be further illustrated below through specific embodiments. The following embodiments are specific implementations of the present invention, but the implementation of the present invention is not limited to the following embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and are included within the protection scope of the present invention.

[0039] Example 1 This embodiment discloses a method for preparing a layered SMNF / MXene-ss composite membrane, including the following steps: Step (1): Add 3.2g of LiF to 40mL of 9mol / L HCl aqueous solution and stir at room temperature for 30min to completely dissolve LiF, thus obtaining LiF / HCl etching solution; 2.0 g of Ti3AlC2MAX phase powder (400 mesh, purchased from Jilin Yiyi Technology Co., Ltd., item number: 22-3-13-1-6-2-14) was added to the above LiF / HCl etching solution and stirred at 36℃ for 24 h. After the reaction was completed, the product was centrifuged at 3500 rpm for 5 min, the supernatant was discarded, and the precipitate was repeatedly washed with 2 mol / L HCl aqueous solution and deionized water until the pH of the system was 6. The obtained precipitate was redispersed in deionized water and ultrasonically exfoliated at 0℃ for 1 h. Then, a high concentration of few-layer MXene aqueous dispersion was obtained by centrifugation and enrichment. The concentration of MXene was 10 mg / mL. 500 mg of sericin powder (purchased from Huzhou Xintiansi Biotechnology Co., Ltd.) was added to 50 mL of MXene aqueous dispersion to make the mass ratio of MXene to sericin 1:1. The mixture was stirred at 300 rpm for 4 h to obtain a sericin-MXene conductive dispersion. Step (2): Place the natural silk in a 5% Na2CO3 aqueous solution, degumm at 100°C for 1 hour at a bath ratio of 1:50, and then take it out. Repeat the above degumming process once. After the degumming process is completed, wash with deionized water until neutral, and dry at 60°C to constant weight to obtain degummed silk. Urea, choline chloride and water were mixed in a molar ratio of 6:3:1 and stirred at 120℃ and 400rpm for 1h to obtain a eutectic solvent system. 1g of degummed silk was added to 100g of eutectic solvent system and subjected to liquid phase exfoliation treatment for 3h at 80℃ and 400 rpm to dissociate the silk fibers into micro-nano-scale fibrils. The treated system was diluted with deionized water and mechanically dispersed at 7000 rpm for 30min at room temperature. Finally, deionized water was added to obtain a silk micro-nano fibrils (SMNF) dispersion. The total amount of deionized water added is 500 mL; Step (3): Take the sericin-MXene conductive dispersion obtained in step (1) as the filtrate for the MXene-SS conductive layer; take the silk micro-nano fiber dispersion obtained in step (2) as the filtrate for the SMNF layer. SMNF dispersion and sericin-MXene conductive dispersion were alternately vacuum filtered in a preset sequence to obtain a wet composite membrane. The specific process of alternating vacuum filtration includes the following steps: The SMNF dispersion was added to a vacuum filtration device (the vacuum pump was a circulating water vacuum pump with a power of 180W; the filter membrane was a PCTE polycarbonate filter membrane with a thickness of 0.2µm and a pore size of 47mm) for the first filtration, forming a first SMNF layer on the filter membrane surface; the sericin-MXene conductive dispersion was added to the same filtration device for the second filtration, forming a first MXene-SS conductive layer on the first SMNF layer; the SMNF dispersion was added again for the third filtration, forming a second SMNF layer on the first MXene-SS conductive layer. Step (4): Peel the wet composite membrane off the filter membrane and dry it at 25°C to obtain a layered SMNF / MXene-ss composite membrane with an alternating structure of SMNF layer / MXene-ss conductive layer / SMNF layer, which is referred to as the 2+1 layer sample.

[0040] The SMNF / MXene-ss composite film prepared in Example 1 above has a distinct cross-layered structure and possesses both conductivity and flexibility.

[0041] Example 2 This embodiment discloses a method for preparing a layered SMNF / MXene-ss composite membrane, including the following steps: Step (1): Add 3.2g of LiF to 40mL of 9mol / L HCl aqueous solution and stir at room temperature for 30min to completely dissolve LiF, thus obtaining LiF / HCl etching solution; 2.0 g of Ti3AlC2MAX phase powder (400 mesh, purchased from Jilin Yiyi Technology Co., Ltd.) was added to the above LiF / HCl etching solution and stirred at 36℃ for 24 h. After the reaction was completed, the product was centrifuged at 3500 rpm for 5 min, the supernatant was discarded, and the precipitate was repeatedly washed with 2 mol / L HCl aqueous solution and deionized water until the pH of the system was 6. The obtained precipitate was redispersed in deionized water and ultrasonically exfoliated at 0℃ for 1 h. Then, a high concentration of few-layer MXene aqueous dispersion was obtained by centrifugation. Sericin powder (purchased from Huzhou Xintiansi Biotechnology Co., Ltd.) was added to MXene aqueous dispersion to make the mass ratio of MXene to sericin 1:1. The mixture was stirred at 300 rpm for 4 hours to obtain a sericin-MXene conductive dispersion. Step (2): Place the natural silk in a 5% Na2CO3 aqueous solution, degumm at 100°C for 1 hour at a bath ratio of 1:50, and then take it out. Repeat the above degumming process once. After the degumming process is completed, wash with deionized water until neutral, and dry at 60°C to constant weight to obtain degummed silk. Urea, choline chloride and water were mixed in a molar ratio of 6:3:1 and stirred at 120℃ and 400rpm for 1h to obtain a eutectic solvent system. 1g of degummed silk was added to 100g of eutectic solvent system and liquid phase exfoliation was performed under stirring to dissociate the silk fibers into micro-nano fibrils. The treated system was diluted with deionized water and mechanically dispersed at 7000rpm for 30min to obtain a silk micro-nano fibrils (SMNF) dispersion. Step (3): Take the sericin-MXene conductive dispersion obtained in step (1) as the filtrate for the MXene-SS conductive layer; take the silk micro-nano fiber dispersion obtained in step (2) as the filtrate for the SMNF layer. SMNF dispersion and sericin-MXene conductive dispersion were alternately vacuum filtered in a preset sequence to obtain a wet composite membrane. The specific process of alternating vacuum filtration includes the following steps: The SMNF dispersion was added to a vacuum filtration apparatus (a circulating water vacuum pump with a power of 180W; a PCTE polycarbonate filter membrane with a thickness of 0.2µm and a pore size of 47mm) for the first filtration, forming a first SMNF layer on the filter membrane surface. A sericin-MXene conductive dispersion was then added to the same filtration apparatus for a second filtration, forming a first MXene-SS conductive layer on the first SMNF layer. A third filtration was performed with the addition of SMNF dispersion, forming a second SMNF layer on the first MXene-SS conductive layer. A fourth filtration was performed with the addition of sericin-MXene conductive dispersion, forming a second MXene-SS conductive layer on the second SMNF layer. Finally, a fifth filtration was performed with the addition of SMNF dispersion, forming a third SMNF layer on the second MXene-SS conductive layer. Step (4): Peel the wet composite membrane off the filter membrane and dry it at 25°C to obtain a layered SMNF / MXene-ss composite membrane with an alternating structure of SMNF layer / MXene-ss conductive layer / SMNF layer / MXene-ss conductive layer / SMNF layer, which is denoted as 3+2 layer sample.

[0042] The SMNF / MXene-ss composite film prepared in Example 2 above has an obvious cross-layered structure and the fracture surface shows an obvious layered stacked structure. The MXene-ss conductive layer and the SMNF layer form a multi-level interface bond, which is beneficial to prolong the crack propagation path and improve mechanical properties.

[0043] Comparative Example 1 This comparative example discloses a method for preparing a pure SMNF membrane, including the following steps: Step (1): Take the silk micro-nano fibril dispersion as the filtrate for the SMNF layer; The preparation method of the silk micro-nano fibril dispersion is the same as that in Example 1; The SMNF dispersion was added to a vacuum filtration device (the vacuum pump was a circulating water vacuum pump with a power of 180W; the filter membrane was a PCTE polycarbonate filter membrane with a thickness of 0.2um and a pore size of 47mm) for vacuum filtration to obtain a wet membrane; Step (4): Peel the wet composite membrane off the filter membrane and dry it at 25°C to obtain a pure SMNF membrane.

[0044] The pure SMNF film prepared in Comparative Example 1 above has a certain degree of flexibility, but does not contain MXene conductive components and cannot form a stable conductive network.

[0045] Comparative Example 2 This comparative example discloses a method for preparing a homogeneous mixed SMNF / MXene-ss composite membrane, comprising the following steps: Step (1): Take sericin-MXene conductive dispersion as the filtrate for MXene-SSS conductive layer; take silk micro-nano fibril dispersion as the filtrate for SMNF layer. The preparation methods of sericin-MXene conductive dispersion and silk micro / nano fiber dispersion are the same as in Example 1; After mixing SMNF dispersion and sericin-MXene conductive dispersion at a volume ratio of 2:1, the mixture was vacuum filtered in one step (the vacuum pump was a circulating water vacuum pump with a power of 180W; the filter membrane was a PCTE polycarbonate filter membrane with a thickness of 0.2um and a pore size of 47mm) to obtain a wet composite membrane. Step (2): Peel the wet composite membrane off the filter membrane and dry it at 25°C to obtain a single-layer SMNF / MXene-ss composite membrane.

[0046] The SMNF / MXene-ss composite membrane prepared in Comparative Example 2 is a homogeneous composite membrane. In this homogeneous composite membrane, the conductive components are randomly separated by the SMNF network, resulting in poor continuity of the conductive pathway and poor ability to block layered cracks. The mechanical reinforcement effect is lower than that of the layered filtration composite membrane.

[0047] Experimental data characterization and performance testing (1) Structural characterization The surface morphology of the SMNF / MXene-ss composite film prepared in Example 1 and the pure SMNF film prepared in Comparative Example 1 were observed using scanning electron microscopy, as well as the fracture surface structure of the SMNF / MXene-ss composite film prepared in Example 2 and the pure SMNF film prepared in Comparative Example 1. Figure 1 and Figure 2 As shown.

[0048] Figure 1 Image a is a scanning electron microscope image of the pure SMNF film prepared in Comparative Example 1. Figure 1 Image b is a scanning electron microscope (SEM) image of the SMNF / MXene-ss composite film prepared in Example 1. From... Figure 1 As can be seen, the surface of the pure SMNF membrane mainly exhibits a fiber network structure with relatively large pores, while the surface of the SMNF / MXene-ss composite membrane is more dense.

[0049] Figure 2 This is a schematic diagram of the fracture surface layered structure of the pure SMNF membrane prepared in Comparative Example 1 and the SMNF / MXene-ss composite membrane prepared in Example 2; from Figure 2 As can be seen from this, compared with the pure SMNF membrane prepared in Comparative Example 1 ( Figure 2 a) The fracture surface of the SMNF / MXene-ss composite film prepared in Example 2 exhibits a distinct layered stacked structure. Figure 2(b) This is because MXene sheets are dispersed in the SMNF network and tightly bonded to the fibers, thus demonstrating that layered filtration can effectively construct a mother-of-pearl-like layered composite structure.

[0050] The distribution of C, N, O, and Ti elements in the SMNF / MXene-ss composite membrane prepared in Example 1 and the pure SMNF membrane prepared in Comparative Example 1 were determined using EDS elemental distribution analysis. The test results are as follows: Figure 3 and Figure 4 As shown.

[0051] Figure 3 This is a graph showing the EDS elemental distribution results of the pure SMNF membrane prepared in Comparative Example 1. Figure 4 This is a graph showing the EDS elemental distribution test results of the SMNF / MXene-ss composite membrane prepared in Example 1.

[0052] Will Figure 3 and Figure 4 A comparison reveals that, Figure 4 The presence of a significant Ti element signal in the SMNF / MXene-ss composite film prepared in Example 1 indicates the successful introduction of MXene. Simultaneously, the retention of C, N, and O element signals suggests the continued existence of the SMNF matrix structure. Therefore, Figure 3 and Figure 4 The results showed that C, N and O elements originated from SMNF and sericin, while Ti element originated from MXene. Ti element was relatively uniformly distributed in the SMNF / MXene-ss composite film, indicating that the MXene-ss conductive component was successfully introduced into the SMNF / MXene-ss composite film and formed a stable composite network.

[0053] The interfacial interactions of the SMNF / MXene-ss composite membrane were further analyzed using FTIR and XPS. The test results are as follows: Figure 5 and Figure 6 As shown.

[0054] Figure 5 The graphs show the FTIR test results of the pure SMNF membrane prepared in Comparative Example 1 and the SMNF / MXene-ss composite membrane prepared in Example 1. Figure 6 The graph shows the XPS test results of the pure SMNF membrane prepared in Comparative Example 1 and the SMNF / MXene-ss composite membrane prepared in Example 1.

[0055] from Figure 5 As can be seen, both the pure SMNF membrane prepared in Comparative Example 1 and the SMNF / MXene-ss composite membrane prepared in Example 1 exhibit typical protein characteristic peaks, indicating that the SMNF host structure remains intact after layered composite formation; 3278 cm⁻¹ -1Intensity variation of peak positions in the vicinity and related regions of amide / CO / CN (3278 cm⁻¹) - ¹, corresponding to the OH / NH stretching vibration, is the region most sensitive to hydrogen bonding; 2925 cm⁻¹ - ¹, corresponding to CH stretching vibration; 1619 cm - ¹ and 1511 cm - ¹, can be attributed to the protein amide-related vibrational region, which mainly reflects changes near amide I and amide II; 1226 cm - ¹ and 1065 / 1067 cm - ¹, mainly related to the vibrations of CN, CO and other groups), indicating a hydrogen bonding interaction between SMNF and MXene-ss; in addition, the low wavenumber region (608 cm⁻¹ in the figure) of the SMNF / MXene-ss composite film - ¹ and 541 / 546 cm - The absorption peaks near ¹ change. This region is usually related to the vibration of the MXene surface end groups or key phases. Therefore, the peak changes that appear or are enhanced in this region of the composite film can serve as evidence of the successful introduction of MXene-ss and the existence of interfacial interactions, indicating that there may be interfacial coupling between the SMNF layer and the MXene-ss conductive layer.

[0056] from Figure 6 As can be seen from the results, the Ti 2p characteristic peak appears in the SMNF / MXene-ss composite membrane prepared in Example 1, indicating that MXene has been successfully introduced; at the same time, the C, N and O signals are all preserved, indicating that the SMNF protein matrix structure is intact in the SMNF / MXene-ss composite membrane.

[0057] In summary, from Figure 5 and Figure 6 It can be seen that the presence of protein characteristic peaks and MXene-related element signals in the SMNF / MXene-ss composite membrane indicates that there are hydrogen bonds, physical entanglement and interfacial coupling between SMNF, sericin and MXene.

[0058] (2) Mechanical property testing The tensile properties of the pure SMNF film prepared in Comparative Example 1, the SMNF / MXene-ss composite film prepared in Example 1, and the SMNF / MXene-ss composite film prepared in Example 2 were tested using a universal testing machine. The test results are as follows: Figure 7 As shown.

[0059] Figure 7 The test results show that the maximum tensile strength of the pure SMNF film prepared in Comparative Example 1 is 34.5 MPa, and the elongation at break is 5.1%. Figure 7(a) The maximum tensile strength of the SMNF / MXene-ss composite membrane (2+1 layer sample) prepared in Example 1 was 59.3 MPa, and the elongation at break was 7.1%. Figure 7 (b) The maximum tensile strength of the SMNF / MXene-ss composite membrane (3+2 layer sample) prepared in Example 2 was 104.1 MPa, and the elongation at break was 11.2%. Figure 7 (c). The above results indicate that the SMNF / MXene-ss layered structure constructed by layered filtration can significantly improve the mechanical strength and ductility of the composite membrane. The enhancement mechanism is as follows: the SMNF layer, as a flexible reinforcing skeleton, can bear the external load and prevent the rapid propagation of cracks; the MXene-ss layer, as a lamellar functional phase, can improve the membrane compactness and form a multi-level interface; and the sericin, as an interface regulating component, can enhance the binding force between MXene and SMNF, thereby achieving a synergistic improvement in strength and toughness.

[0060] To verify the effect of homogeneous mixing on the mechanical properties of the constructed SMNF / MXene-ss composite membrane, this invention further characterized the homogeneous mixed SMNF / MXene-ss composite membrane prepared in Comparative Example 2. Experimental results showed that when SMNF, sericin, and MXene were directly homogeneously mixed and then filtered, the system struggled to form a complete, continuous, and stable membrane layer. The resulting sample was loose and fragmented, exhibiting poor overall integrity, and a self-supporting composite membrane that could be stably peeled off and characterized could not be obtained. Figure 7 (d). Therefore, it is difficult to conduct further standard mechanical property tests on this comparative sample. The above experimental phenomena show that, even if the composition is similar to the SMNF / MXene-ss composite film prepared in the examples, it is difficult to achieve effective film formation and obtain the structure and properties corresponding to the examples by simply using a homogeneous mixing method.

[0061] In summary, the layered filtration method is used to construct the multilayer structure in this embodiment of the invention because this method enables the layer-by-layer deposition and in-situ coupling of different components during continuous filtration, thereby forming a composite structure with clear layers, tight interfaces, and overall continuity. In this process, SMNF forms a scaffold support, sericin plays a role in interface regulation and bridging stability, and MXene forms a relatively continuous conductive layer or conductive pathway. The synergistic effect of these three components is more conducive to obtaining a complete membrane layer, endowing the composite membrane with superior overall performance. Therefore, the SMNF / MXene-ss composite membrane prepared by the layered filtration method exhibits better overall structural continuity and mechanical properties than that prepared by the homogeneous mixing method.

[0062] (3) Conductivity test The conductivity of the SMNF / MXene-ss composite film prepared in Example 1 and Example 2 was tested, and the test results are as follows: Figure 8 As shown.

[0063] Figure 8 a is the SMNF / MXene-ss composite membrane prepared in Example 1 (i.e. Figure 8 The LSV curve of the 2+1 layer in Example 2 is shown in Figure b. Figure 8 The LSV curve of the 3+2 layer in Example 1 is shown in Figure c, where c is the SMNF / MXene-ss composite membrane prepared in Example 1 (i.e., the 3+2 layer). Figure 8 The 2+1 layers in Example 2 and the SMNF / MXene-ss composite membrane prepared in Example 2 (i.e., Figure 8 A comparative analysis of the surface resistance of the 3+2 layers in the diagram.

[0064] The LSV curves were measured using an electrochemical workstation, and the detection method was linear sweep voltammetry (LSV). During testing, the composite membrane sample was cut into 2... The sample is 2cm in size and fixed on the test fixture. The two ends of the sample are used as electrodes to connect to the test system. The sample is linearly scanned according to the set voltage range under room temperature conditions, and the response relationship between the current and the applied voltage is recorded in real time to obtain the LSV curve.

[0065] from Figure 8 As can be seen from a and b, both composite films prepared in Example 1 and Example 2 exhibit stable linear current-voltage responses. However, the current response of the 2+1 layer sample prepared in Example 1 is significantly higher than that of the 3+2 layer sample prepared in Example 2, indicating that different layered structures in the composite film have a significant impact on charge transport and interfacial polarization behavior.

[0066] from Figure 8 As can be seen from Figure c, the surface resistance of the 2+1 layer sample prepared in Example 1 is significantly lower than that of the 3+2 layer sample prepared in Example 2. Test results show that the average surface resistance of the 2+1 layer sample is approximately 2.65 Ω / □, while the average surface resistance of the 3+2 layer sample is approximately 38.6 Ω / □. The former is only about 1 / 14.6 of the latter, indicating that the 2+1 layer sample has a more continuous and efficient in-plane conductive path. Simultaneously, the current response of the 2+1 layer sample at 1.0 V in the LSV test is also significantly higher than that of the 3+2 layer sample, further demonstrating that the 2+1 layer sample has stronger carrier transport capability and better electrical conductivity.

[0067] In summary, the 2+1 layer sample prepared in Example 1 outperformed the 3+2 layer sample prepared in Example 2 in terms of surface conductivity and current response, indicating that a fewer layer count results in a more continuous conductive network, which is more conducive to electron transport. Although the 3+2 layer sample prepared in Example 2 has higher surface resistance and weaker conductivity, the increased number of interlayer interfaces enhances the multiple reflections of electromagnetic waves and reduces interfacial polarization losses.

[0068] (4) Electromagnetic shielding performance test The electromagnetic shielding performance of the SMNF / MXene-ss composite film prepared in Example 1 and the pure SMNF film prepared in Comparative Example 1 in the X-band was tested using a vector network analyzer. The test results are as follows: Figure 9 As shown.

[0069] from Figure 9 As can be seen, the shielding performance of the pure SMNF film prepared in Comparative Example 1 is generally low, indicating that the pure silk micro / nano fibrillary film has virtually no blocking ability for electromagnetic waves. When MXene-ss is introduced, the SE of the SMNF / MXene-ss composite film prepared in Example 1 is significantly improved, reaching 32-39 dB overall, indicating that the highly conductive MXene sheets can significantly enhance the electromagnetic wave reflection and conduction loss of the composite film.

[0070] The results show that the SMNF / MXene-ss layered composite film prepared by this invention can not only be used to prepare rewritable conductive paper, but also as a flexible electromagnetic shielding material for smart packaging, wearable devices and electronic device protection.

[0071] (5) Humidity sensing performance test The humidity sensing performance of the SMNF / MXene-ss composite film (3+2 layer sample) prepared in Example 2 was tested, and the test results are as follows: Figure 10 As shown. The specific test method is as follows: The SMNF / MXene-ss composite membrane prepared in Example 2 was cut into 3×1cm strips, and conductive electrodes were connected to both ends to test its resistance response performance under different relative humidity environments. Different relative humidity environments were constructed sequentially using saturated magnesium chloride aqueous solution, saturated potassium carbonate aqueous solution, saturated sodium bromide aqueous solution, saturated sodium chloride aqueous solution, saturated potassium chloride aqueous solution, and saturated potassium sulfate aqueous solution, corresponding to 33%, 43%, 59%, 75%, 85%, and 97% RH, respectively. The samples were placed in different humidity environments, and after the resistance readings stabilized, their resistance values ​​were recorded, and the relationship between relative humidity and resistance was analyzed.

[0072] from Figure 10As can be seen from Figure a, as the relative humidity increases from 33% RH to 97% RH, the resistance of the SMNF / MXene-ss composite membrane prepared in Example 2 gradually increases from approximately 35.7 Ω to approximately 43.7 Ω, exhibiting a significant humidity response characteristic. Within the 33% to 97% RH range, the resistance of the SMNF / MXene-ss composite membrane prepared in Example 2 shows a good linear relationship with relative humidity, with a linear fitting equation of Y = 0.1207X + 31.79747 and a correlation coefficient R² = 0.99024. This indicates that the SMNF / MXene-ss composite membrane has good response sensitivity and linear recognition ability to changes in environmental humidity.

[0073] Furthermore, the SMNF / MXene-ss composite membrane prepared in Example 2 was subjected to a cyclic humidity response test, and the test results are as follows: Figure 10 As shown in b. From Figure 10 As can be seen from b, when the ambient humidity alternates between different relative humidity conditions, the resistance of the SMNF / MXene-ss composite film prepared in Example 2 increases with increasing humidity and gradually recovers after the humidity decreases, exhibiting good reversibility and repeatability. Therefore, the SMNF / MXene-ss composite film prepared in the embodiments of the present invention can be used as a humidity-responsive conductive functional material for humidity sensing, respiratory monitoring, paper-based sensors, and wearable flexible electronic devices.

[0074] To verify the effect of homogeneous mixing on the humidity sensing performance of the constructed SMNF / MXene-ss composite membrane, this invention further characterized the homogeneous mixed SMNF / MXene-ss composite membrane prepared in Comparative Example 2. Experimental results showed that when SMNF, sericin, and MXene were directly homogeneously mixed and then filtered, the system struggled to form a complete, continuous, and stable membrane layer. The resulting sample was loose and fragmented, with poor overall integrity, making it impossible to obtain a stable, peelable, and characterizable self-supporting composite membrane (see...). Figure 7 (d). Therefore, it is difficult to conduct further standardized humidity sensing performance tests on this comparative sample. The above experimental phenomena show that, even if the composition of the components is similar to that of the SMNF / MXene-ss composite film prepared in the examples, it is difficult to achieve effective film formation and obtain the structure and performance corresponding to the examples by simply using a homogeneous mixing method. The reason is that the distribution of each component in the homogeneous mixing system is relatively random, the interface construction is not clear, the MXene conductive phase is difficult to form a stable and continuous path, the moisture transmission path and the electrical signal modulation process are not orderly enough, and the overall structural stability is poor, which is not conducive to obtaining a sensitive, stable and repeatable humidity response.

[0075] In summary, the superior humidity sensing performance of the SMNF / MXene-ss composite membrane prepared in this embodiment of the invention is due to the combined effect of the composite membrane's structural design and the synergistic effect of the materials. Specifically, SMNF, sericin, and MXene have a synergistic effect, and the SMNF / MXene-ss composite membrane exhibits a multilayered alternating structure.

[0076] Furthermore, SMNF, as a fiber network framework, possesses a certain porous structure and a large contact interface, which is conducive to the adsorption and diffusion of water molecules in the environment. Sericin contains many hydrophilic groups, which can enhance the system's sensitive response to humidity changes. MXene provides a conductive pathway, enabling the interfacial interactions and charge transport changes caused by humidity changes to be converted into detectable electrical signals. As the relative humidity increases, water molecules gradually adsorb onto the surface of the SMNF / MXene-ss composite membrane and further penetrate into the MXene sheets and the SMNF / MXene-ss interface region, increasing the spacing between conductive sheets and hindering electron transport pathways, thus increasing the resistance of the composite membrane. When the humidity decreases, the adsorbed water molecules gradually desorb, the spacing between sheets and the conductive pathway tend to recover, and the resistance value decreases accordingly. Therefore, in this embodiment of the invention, a multilayer composite membrane is constructed using a layered filtration method, making the spatial distribution, interfacial contact, and mass transfer / conduction pathways of the above components more ordered, thereby being more conducive to the occurrence of the humidity response process and stable signal output.

[0077] (6) Respiratory monitoring performance test The respiratory monitoring performance of the SMNF / MXene-ss composite membrane prepared in Example 2 was tested, and the test results are as follows: Figure 11 As shown. The specific test method is as follows: The SMNF / MXene-ss composite membrane prepared in Example 2 was cut into 3×1cm strips, and conductive electrodes were connected to both ends of the strips to construct a resistive respiratory monitoring device. During testing, the sample was placed near the mouth and nose of a human or fixed to the surface of a mask, and its response to respiratory airflow was evaluated by recording the change in the relative resistance of the sample during human breathing.

[0078] like Figure 11 As shown, the SMNF / MXene-ss composite membrane prepared in Example 2 exhibits a significant dynamic resistance response during human respiration. During exhalation, the exhaled air contains a high concentration of water molecules, which adsorb onto the surface of the SMNF / MXene-ss composite membrane and between the MXene sheets, altering the conductive pathway and causing an increase in relative resistance. When exhalation ends or during inhalation, the adsorbed water molecules gradually desorb, and the membrane resistance gradually recovers. Therefore, the relative resistance of the SMNF / MXene-ss composite membrane can fluctuate periodically with the respiration process.

[0079] Furthermore, from Figure 11 As can be seen, the peak shape, peak spacing, and response frequency of the composite membrane's relative resistance change curve change with the respiratory rate. At a faster respiratory rate, the interval between resistance response peaks shortens; at a slower respiratory rate, the interval between resistance response peaks increases. This result indicates that the SMNF / MXene-ss layered composite membrane can respond to changes in human respiratory rhythm in real time and can be used to distinguish different respiratory states. The response mechanism is as follows: the MXene-ss conductive layer in the SMNF / MXene-ss composite membrane provides a continuous conductive network, while the SMNF layer provides flexible support and water molecule adsorption channels. Changes in humidity caused by human exhalation affect the MXene layer spacing and interfacial conductive paths, leading to a reversible change in the composite membrane's resistance.

[0080] Therefore, the SMNF / MXene-ss composite film prepared by this invention can be used as a humidity-responsive flexible sensing material for respiratory monitoring, human health monitoring, mask-type sensors, and paper-based flexible electronic devices.

[0081] (7) Thermal management performance test The SMNF / MXene-ss composite film prepared in Example 2 was applied to the surface of a simulated heat source on human skin, and the surface temperature change was observed using an infrared thermal imager. Figure 12 As shown, the skin temperature on the left is 34.1℃, while the temperature on the right, where the SMNF / MXene-ss composite film covers the skin surface, is 31.6℃. The temperature on the outer side of the composite film is lower, meaning less heat is transferred from the skin to the outer surface of the composite film. This is because the MXene sheets have a conductive network and infrared radiation modulation capabilities, allowing the SMNF / MXene-ss composite film to reduce heat loss to the outside, thus exhibiting a certain thermal insulation effect.

[0082] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.

Claims

1. A method for preparing a stratified filtration SMNF / MXene-SS composite membrane, characterized in that, Includes the following steps: Sericin was added to MXene aqueous dispersion and dispersed evenly to obtain a sericin-MXene conductive dispersion; Degummed silk was added to a eutectic solvent for liquid phase exfoliation, and then water was added to disperse it evenly to obtain a silk micro-nano fibril dispersion. Sericin-MXene conductive dispersion was used as the filtrate for the MXene-SSS conductive layer; silk micro-nano fibril dispersion was used as the filtrate for the SMNF layer. The SMNF dispersion and the sericin-MXene conductive dispersion were alternately vacuum filtered in layers, so that the SMNF layer and the MXene-ss conductive layer were deposited one after another, forming a structure in which the SMNF layer and the MXene-ss conductive layer were arranged alternately. After peeling and drying, the layered filtration SMNF / MXene-ss composite membrane was obtained.

2. The method for preparing the stratified SMNF / MXene-SS composite membrane according to claim 1, characterized in that, When preparing the sericin-MXene conductive dispersion, the mass ratio of MXene to sericin protein is (0.8-1.2):1; the concentration of the MXene aqueous dispersion is 8-12 mg / mL.

3. The method for preparing the stratified SMNF / MXene-SS composite membrane according to claim 1, characterized in that, The specific process for preparing the sericin-MXene conductive dispersion to ensure uniform dispersion includes stirring at a speed of 250-350 rpm for 3-5 hours.

4. The method for preparing the stratified SMNF / MXene-ss composite membrane according to claim 1, characterized in that, When preparing the silk micro-nano fibril dispersion, the mass ratio of degummed silk to eutectic solvent is 1:(90-110).

5. The method for preparing the stratified SMNF / MXene-ss composite membrane according to claim 1, characterized in that, The specific process for preparing the silk micro-nano fibril dispersion includes the following steps: liquid phase exfoliation temperature of 70-90℃, stirring speed of 300-500 rpm, and treatment time of 2-4 h.

6. The method for preparing the stratified filtration SMNF / MXene-ss composite membrane according to claim 1, characterized in that, The specific process for preparing the silk micro-nano fibril dispersion includes: mechanical dispersion at a speed of 6500-7500 rpm for 20-40 minutes.

7. The method for preparing the stratified filtration SMNF / MXene-ss composite membrane according to claim 1, characterized in that, The preparation process of the eutectic solvent for the silk micro / nano fiber dispersion includes the following steps: mixing urea, choline chloride and water in a molar ratio of (5.5-6.5):(2.5-3.5):(0.8-1.2) and stirring at a temperature of 110-130℃ and a speed of 350-450 rpm for 0.5-1 h.

8. The method for preparing the stratified filtration SMNF / MXene-ss composite membrane according to claim 1, characterized in that, The specific process of alternating vacuum filtration includes the following steps: The SMNF dispersion and the sericin-MXene conductive dispersion were arranged in a layer sequence with alternating SMNF and MXene-SS conductive layers, and the outermost layer was always an SMNF layer. The layers were then subjected to alternating vacuum filtration to deposit and composite the layers sequentially.

9. A layered filtration SMNF / MXene-ss composite membrane prepared by the method described in any one of claims 1-8.

10. The application of the layered filtration SMNF / MXene-ss composite membrane as described in claim 9 on rewritable conductive paper, paper-based circuits, humidity sensing materials, flexible electromagnetic shielding materials, or thermal management materials.